Smashing HTML5 - Sanders, William B., 1944- (Smashing magazine book series., 2011)
"The ultimate guide to HTML 5 from the world-renowned Smashing Magazine HTML 5 is the newest version of HTML, the foundation upon which nearly all Web sites are built. This latest iteration boasts exciting new features and capabilities, including the fact that it is the only way to display video content on Apple's mobile devices. This must-have guide delivers all the HTML 5 information you need to get up and running quickly with building next-generation Web sites. Details the latest features and capabilities of the new HTML 5 Reviews HTML 5 tags, forms, and navigation strategies Shows you how to integrate media--including video--into HTML 5 pages Encourages you to harness the power of the HTML 5 canvas Explains how to create interactivity and store information Smashing HTML 5 teaches you how to build successful Web sites quickly with HTML 5"--